The IgCAM CLMP regulates expression of Connexin43 and Connexin45 in intestinal and ureteral smooth muscle contraction in mice - Hanna Langhorst; René Jüttner; Dieter Groneberg; Azadeh Mohtashamdolatshahi; Laura Pelz; Bettina Purfürst; Kai M. Schmidt-Ott; Andreas Friebe; Fritz G. Rathjen (The Company of Biologists, 2018)
CAR-like membrane protein (CLMP), an immunoglobulin cell adhesion molecule (IgCAM), has been implicated in congenital short-bowel syndrome in humans, a condition with high mortality for which there is currently no cure. We therefore studied the function of CLMP in a Clmp-deficient mouse model. Although we found that the levels of mRNAs encoding Connexin43 or Connexin45 were not or were only marginally affected, respectively, by Clmp deficiency, the absence of CLMP caused a severe reduction of both proteins in smooth muscle cells of the intestine and of Connexin43 in the ureter. Analysis of calcium signaling revealed a disordered cell-cell communication between smooth muscle cells, which in turn induced an impaired and uncoordinated motility of the intestine and the ureter. Consequently, insufficient transport of chyme and urine caused a fatal delay to thrive, a high rate of mortality, and provoked a severe hydronephrosis in CLMP knockouts. Neurotransmission and the capability of smooth muscle cells to contract in ring preparations of the intestine were not altered. Physical obstructions were not detectable and an overall normal histology in the intestine as well as in the ureter was observed, except for a slight hypertrophy of smooth muscle layers. Deletion of Clmp did not lead to a reduced length of the intestine as shown for the human CLMP gene but resulted in gut malrotations. In sum, the absence of CLMP caused functional obstructions in the intestinal tract and ureter by impaired peristaltic contractions most likely due to a lack of gap-junctional communication between smooth muscle cells.